PERUMUSAN STRATEGI BERSAING DENGAN MENGGUNAKAN STRATEGY FORMULATION FRAMEWORK - Permadi, Muhammad Daffa Lazuardi (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to apply the strategy formulation framework in arranging a competitive strategy for Barakesna coffee shop and angkringan. The object of this qualitative descriptive research is Barakesna, a coffee shop with Javanese concept in Malang City, East Java. Barakesna coffee shop and angkringan is a food-and-beverage business that is currently engaged in an increasing competition. This research starts by conducting external environment analysis to identify the business’ opportunities and threats, followed by internal environment analysis to identify its strengths and weaknesses. The result of this analysis was used as the input for IE matrix, SWOT matrix, and QSPM analyses. Based on the outcome of the analysis using IFE and EFE matrix, the observation continued to the IE matrix, which suggests that Barakesna is on the fifth cell, indicating that the company is in hold-and-maintain condition. Then, the results of the QSPM analysis show that market penetration is the suggested strategy with the TAS score of 5.05. The company is advised to focus its business strategy on massively enhancing the market share of its products. The implementation of this strategy is believed to be helpful for the business to increase its competitiveness amid the fierce competition.